12f-15=12f-15

Simple and best practice solution for 12f-15=12f-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12f-15=12f-15 equation:


Simplifying
12f + -15 = 12f + -15

Reorder the terms:
-15 + 12f = 12f + -15

Reorder the terms:
-15 + 12f = -15 + 12f

Add '15' to each side of the equation.
-15 + 15 + 12f = -15 + 15 + 12f

Combine like terms: -15 + 15 = 0
0 + 12f = -15 + 15 + 12f
12f = -15 + 15 + 12f

Combine like terms: -15 + 15 = 0
12f = 0 + 12f
12f = 12f

Add '-12f' to each side of the equation.
12f + -12f = 12f + -12f

Combine like terms: 12f + -12f = 0
0 = 12f + -12f

Combine like terms: 12f + -12f = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 | | V=pir | | 20y=13000 | | 10-3s=s | | 2(x-5)-(3x+6)=-12 | | -1=-6x+5x+5 | | 4x-2x+4=24 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=f(x) | | -1=-6x | | 3x+-7=8+6(x+2) | | 8n-1(2n-3)= | | -5n-7=3n+41 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=0 | | 4p=63 | | 4(y-1)=4 | | 12=0.25(R) | | 6x^2+21x= | | 9(2m-3)-4(5+3m)=5 | | 4n+3+n=43 | | 4(x-4)+3(1+5x)=-32 | | 22=-was | | 36=-9(6+1) | | -16t^2+76t+5=12t+5 | | 50+85+x=180 | | -27+15-22x=31 | | -3(-c-6)=3c-6 |

Equations solver categories